Applications of Knowledge Based Systems in Mining Engineering - R. V. Ramani (The Southern African Institute of Mining and Metallurgy, 1987)
Managers need quality information for effective decision making. This demand, at the present time, is being fulfilled by the increased use of computers via information systems, decision support systems and management information systems. The idea of incorporating intelligence into computers to aid decision-makers has been evolving for over two decades. In recent years, significant progress is reported on applications to business and sciences. In engineering functions, the Artificial Intelligence approach that seems to have great potential is the application of Knowledge Based Systems. The primary objective of this paper is to identify domains in mining engineering where application of knowledge based systems could be beneficial. In- corporation of the expertise required during the analysis and interpretation stages of an engineering design problem through knowledge based systems is recognized as an area of significant benefit. To this end, the components of knowledge based systems for mine ventilation and strata control design are described. The potential applications and limitations of knowledge based systems are outlined.